SELAMAT TINGGAL REVOLUSI INDUSTRI 4.0, SELAMAT DATANG REVOLUSI INDUSTRI 5.0 - Puspita, Yenny; Fitriani, Yessi; Astuti, Sri; Novianti, Sri (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— The purpose of this study is to find out and describe how preparedness in welcoming the 5.0 industrial revolution, especially in the field of education. The method used is descriptive qualitative. Based on the results of the discussion it can be concluded that from the presentation and some explanations about education in the industrial revolution 5.0 there is a need for readiness in welcoming and going through it. The industrial revolution is a change in the way of human life and work processes fundamentally, where the advancement of information technology can integrate in the world of life with digital which can have an impact on scientific disciplines. The Industrial Revolution Society 5.0 emphasized the readiness to think more critically, develop creativity. Based on several explanations, the authors conclude that it is indeed necessary and important for the community to prepare themselves to welcome and carry out the education of the industrial revolution 5.0 with a way of thinking that must always be introduced and accustomed to is a way of thinking to adapt in the future, namely analytical, critical, and creative. Keywords— Education, revolution, industry 5.0 Abstrak—Tujuan penelitian ini adalah untuk mengetahui dan mendeskripsikan bagaimana kesiapan dalam menyambut revolusi industri 5.0 terkhusus dalam bidang pendidikan. Metode yang digunakan adalah deskriptif kualitatif. Berdasarkan hasil pembahasan dapat disimpulkan bahwa dari pemaparan dan beberapa penjelasan mengenai pendidikan pada revolusi industri 5.0 perlu adanya kesiapan dalam menyambut maupun akan menjalaninya. Revolusi industri merupakan sebuah perubahan cara hidup manusia dan proses kerja secara fundamental, dimana adanya kemajuan teknologi informasi dapat mengintegrasikan dalam dunia kehidupan dengan digital yang dapat memberikan dampak disiplin ilmu. Masyarakat revolusi industri 5.0 ditekankan pada kesiapan untuk lebih berpikir kritis, mengembangkan kreativitas. Berdasarkan dari beberapa penjelasan, penulis menyimpulkan bahwa memang perlu dan penting masyarakat menyiapkan diri dalam menyambut dan menjalankan pendidikan revolusi industri 5.0 dengan Cara berpikir yang harus selalu dikenalkan dan dibiasakan adalah cara berpikir untuk beradaptasi di masa depan, yaitu analitis, kritis, dan kreatif. Kata kunci— Pendidikan, revolusi, industri 5.0